DIVERSITY AND SCREENING OF POTENT ACTINOMYCETES FROM THE MARINE ENVIRONMENT - Nisha R.I. and Samuel, *Gnana Prakash Vincent, (Chelonian Research Foundation, 2023)
To evaluate the antimicrobial activity of Actinomycetes species isolated from marine environment. Five fifty nine strains of Actinomycetes were isolated from the samples collected from Marine environment Rajakkamangalam, Thengapatinam, Manakudy, Tirechendur and Manapad. Both soil sediments and associated actinomycetes were isolated. Preliminary screening was done using cross-streak method against gram-positive and gram-negative bacteria. The most potent strains MA7 were selected based on the antibacterial screening and antognostic effect against Pesudomonas sp,. Molecular identification of MA7 as Streptomyces purvas was deposited to GenBank sequence database with the following accession number: OR921611. All those twenty one isolates were active against at least one of the test organisms. Morphological characters were recorded. The results of the present investigation reveal that the marine Actinomycetes from coastal environment are the potent source of novel antibiotics. Isolation, characterization and study of Actinomycetes can be useful in discovery of novel species of Actinomycetes